2016
DOI: 10.4046/trd.2016.79.2.101
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Nocardia farcinica Pneumonia and Mediastinitis in an Immunocompetent Patient

Abstract: Nocardia species are aerobic, gram-positive pathogens found worldwide in soil. Nocardia is considered an opportunistic pathogen, and its infection mostly occurs in immunocompromised patients. We report a case of Nocardia farcinica induced mediastinitis and pneumonia that occurred in a 64-year-old male patient who had no significant medical history except for hypertension. He visited another hospital with a complaint of dyspnea and left chest wall pain. The symptoms arose 7 days ago without any trauma and they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…[23] Although increasing numbers of Nocardia species including N otitidiscaviarum complex have developed increasing resistance and demonstrated inconsistent susceptibility to trimethoprim-sulfamethoxazole, sulfonamides remain the standard antimicrobial agents for the treatment of nocardiosis to date. [24,25] Most N otitidiscaviarum isolates are also reported to be resistant to and beta-lactams like ampicillin, amoxicillin-clavulanic acid, and imipenem, but are usually susceptible to amikacin and the fluoroquinolones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Although increasing numbers of Nocardia species including N otitidiscaviarum complex have developed increasing resistance and demonstrated inconsistent susceptibility to trimethoprim-sulfamethoxazole, sulfonamides remain the standard antimicrobial agents for the treatment of nocardiosis to date. [24,25] Most N otitidiscaviarum isolates are also reported to be resistant to and beta-lactams like ampicillin, amoxicillin-clavulanic acid, and imipenem, but are usually susceptible to amikacin and the fluoroquinolones.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Although the optimal treatment protocol of N otitidiscaviarum still unknown, a combination of sulfonamides and amikacin with a carbapenem or a 3rd-generation cephalosporin are suggested for severe or disseminated infections. [20,23] Similarly in this case, combined therapy (amikacin, imipenem, and trimethoprim-sulfamethoxazole) was administered in accordance with the sensitivity test on the 6th hospital day after N otitidiscaviarum was identified. However, the mortality rate in pulmonary nocardiasis patients is 15% to 30%, even in severe patients up to 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Nocardia genus bacteria are Gram-positive filamentous rod, aerobic pathogens found in soil and water worldwide ( Scharfen et al, 2010 ). They are considered opportunistic pathogens, affecting predominantly immunocompromised patients, including patients with AIDS and transplant recipients ( Kim et al, 2016 ). Pulmonary disease is the most common presentation of Nocardia in immunosuppressed patients and approximately one-third of affected patients have a disseminated disease ( Ambrosioni et al, 2010 ; Kandi, 2015 ; Scorey and Daniel, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found resistance to TMP-SMX in seven of the seventeen (41.2%) cases where antibiotic susceptibility had been performed. Studies have suggested a combination of sulphonamides and amikacin with a carbapenem or a 3 rd generation cephalosporin as optimum therapy for severe or disseminated infections with N. otitidiscaviarum [38,39]. CLSI recommends broth microdilution as a preferred method for susceptibility testing for Nocardia spp.…”
Section: Discussionmentioning
confidence: 99%